Assessing the Bond Strength of Different Luting Cements for Orthodontic Brackets - Narjes Elghezawi; Hanan Mahmoud; Abdussalam Eljabali (AlQalam Journal of Medical and Applied Sciences, 2021)
Aims. The objective of this study was to evaluate and compare tensile bond strength of three adhesives used in orthodontics for bonding brackets to tooth enamel surface. The luting agents used in this investigation were resin-reinforced glass-ionomer cement, light cured composite resin adhesives, and self-etching composite. Methods. Samples of 27 extracted human premolars were divided into three groups equally. In one of the groups, a self-etching primer was applied in accordance with the manufacturer’s instructions and in the other, which were etched with 37% phosphoric acid and bonded in dry field to enamel of buccal surfaces of the teeth with the same adhesive in first group. The debonding force was produced using a universal Instron testing machine with cross head speed of 1 mm/min and tensile bond strength was measured. Results. The self-etching primer presented a lower enamel bond strength value (9.91Mpa) if compared to conventional composite and glass ionomer 13.04Mpa, 12.14MPa respectively. Conclusion. The results obtained revealed no significant differences among adhesive systems. we recommend assessing the bond of different glass ionomer-based cements, as it’s been used hugely used in dental practice.